Competency Exclusion as a Challenge of the Modern Labuor Market – Recommendations and Best Practices (Economic and Political Thought, 2023)
Competency exclusion constitutes one of the key challenges for contemporary societies. Mitigating the negative effects of this phenomenon requires the implementation of appropriate measures. The primary objective of this article is to explore the issue of competency exclusion and to identify best practices and recommendations that can be implemented at various levels of management. This is achieved based on the authors’ analysis of secondary sources, including reports and studies from both Polish and international contexts.
Keywords: competency exclusion, labour market, best practices, competency gap, qualification, education, development